Tissue‐Specific Isolation of Tagged Arabidopsis Plastids. Issue 2 (17th February 2023) - Boussardon, Clément; Keech, Olivier
Abstract: Plastids are found in all plant cell types. However, most extraction methods to study these organelles are performed at the organ level (e.g., leaf, root, fruit) and do not allow for tissue‐specific resolution, which hinders our understanding of their physiology. Therefore, IPTACT (Isolation of Plastids TAgged in specific Cell Types) was developed to isolate plastids in a tissue‐specific manner in Arabidopsis thaliana ( Arabidopsis ). Plastids are biotinylated using one‐shot transgenic lines, and tissue specificity is achieved with a suitable promoter as long as such a promoter exists. Cell‐specific biotinylated plastids are then isolated with 2.8‐µm streptavidin beads. Plastids extracted by IPTACT are suitable for RNA or protein isolation and subsequent tissue‐specific OMICs analyses. This method provides the user with a powerful tool to investigate plastidial functions at cell‐type resolution. Furthermore, it can easily be combined with studies using diverse genetic backgrounds and/or different developmental or stress conditions. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Promoter cloning and plant selection Basic Protocol 2 : Isolation of biotinylated plastids Basic Protocol 3 : Quality control of isolated plastids